On the mechanism of carboxylic acid co-catalyst assisted metalloporphyrin oxidations - Gonsalves, António M. d'A. Rocha (2001)
The role of the carboxylic acid as co-catalyst in metalloporphyrin catalytic hydrogen peroxide oxidations is discussed, taking into account its dependence on the ratio relatively to the catalyst. The catalytic efficiency and stability of the catalyst in the presence of an excess of carboxylic acid suggests that a metallo-acylperoxo complex can be the effective oxidation intermediate.